2022
DOI: 10.32604/cmc.2022.022706
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Joint Key Authentication Model in E-Healthcare

Abstract: Many patients have begun to use mobile applications to handle different health needs because they can better access high-speed Internet and smartphones. These devices and mobile applications are now increasingly used and integrated through the medical Internet of Things (mIoT). mIoT is an important part of the digital transformation of healthcare, because it can introduce new business models and allow efficiency improvements, cost control and improve patient experience. In the mIoT system, when migrating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… Image Registration: To register medical pictures from various periods or modalities, geophysical techniques that align and match multiple datasets are used. This aids in monitoring illness development, evaluating therapy effectiveness, and directing interventions [ 127 , 128 ]. …”
Section: Geophysical Data Analysis In the Health Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“… Image Registration: To register medical pictures from various periods or modalities, geophysical techniques that align and match multiple datasets are used. This aids in monitoring illness development, evaluating therapy effectiveness, and directing interventions [ 127 , 128 ]. …”
Section: Geophysical Data Analysis In the Health Sciencesmentioning
confidence: 99%
“…Medical researchers can make use of the developments achieved in geophysics by modifying and extending computational tools to push the boundaries of medical diagnostics, treatment approaches, and our comprehension of the vast complexity of the human body. This interdisciplinary cooperation enhances diagnostic precision, showcasing the broader implications of technology transfer for advancements in medical research and patient care [ 128 , 129 ].…”
Section: Geophysical Data Analysis In the Health Sciencesmentioning
confidence: 99%
“…Access control [22], [23] anonymizing the data [24], [25], authentication [26], [27], and encryption [28] [29] are the primary methods used in healthcare to protect patient privacy. Authentication methods frequently experience man-in-themiddle attacks.…”
Section: State Of the Art Technologies For Privacy Preservationmentioning
confidence: 99%
“…Sajjad et al [26] suggested a mutual authentication scheme for accessing EHR. They claimed that their protocol has lower computational costs due to a hash function.…”
Section: State Of the Art Technologies For Privacy Preservationmentioning
confidence: 99%
See 1 more Smart Citation